Determination of Reinforced Concrete Rectangular Sections Having Plastic Moments Equal to all IPE Profiles - Beroual, Sayeh; Samai, Mohamed Laid (Civil Engineering Journal, 2021)
The comparison between steel structures and reinforced concrete structures has always been governed by economy and response to earthquake. Steel structures being lighter and are thus more efficient to resist earthquake. On the other hand, they are more expensive (4 to 5 times). Theoretically, two structural elements having the same plastic moment have an equal failure or collapse load. Different profiles of IPE are realized in industry and all their characteristics are determined with a great precision (weight, geometrical characteristics and thus their plastic moment). Determining equivalent rectangular singly reinforced concrete cross-sections is not easy and seems impossible to be solved analytically. To a given profile it may be found a multitude of equivalent rectangular reinforced concrete cross-section (singly and doubly reinforced with different yield strengths and compositions of concrete). To take into consideration all these factors, it is absolutely necessary to construct three axis design charts with an appropriate choice of system of coordinates in order to cover all possible ranges of different parameters. The choice of all these possible rectangular reinforced concrete sections is governed by the plastic performance of these later. They must be under reinforced, allowing plastification of steel before failure in order to permit the redistribution phenomenon in plastic analysis. The exploitation of these different charts has revealed that the absolute majority of these rectangular reinforced concrete cross-section are reasonably well designed and are in conformity with the dimensions used in practice. The results of the present characterization using Eurocode 2 characteristics are compared to those of CP110. The impact does not seem to be very relevant.Â Doi: 10.28991/cej-2021-03091677 Full Text: PDF